2020
DOI: 10.1027/0269-8803/a000253
|View full text |Cite
|
Sign up to set email alerts
|

Social Feedback Valence Differentially Modulates the Reward Positivity, P300, and Late Positive Potential

Abstract: Abstract. Abnormal social or reward processing is associated with several mental disorders. Although most studies examining reward processing have focused on monetary rewards, recent research also has tested neural reactivity to social rewards (e.g., positive social feedback). However, the majority of these studies only include two feedback valences (e.g., acceptance, rejection). Yet, social evaluation is rarely binary (positive vs. negative) and people often give “on the fence” or neutral evaluations of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
(108 reference statements)
4
12
0
Order By: Relevance
“…The present study extended this result to external, social feedback: people are more efficient in voluntarily forgetting information conveying social rejection than social acceptance. At a neural level, our ERP results suggest that such a mnemic neglect effect originated at the encoding stage: negative social feedback elicited smaller LPP amplitudes than positive feedback, which is in line with previous literature on the processing of social emotional materials (Bublatzky et al., 2014; Funkhouser et al., 2020; Gu et al., 2020) and the insufficient integration theory proposed by Pinter et al. (2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study extended this result to external, social feedback: people are more efficient in voluntarily forgetting information conveying social rejection than social acceptance. At a neural level, our ERP results suggest that such a mnemic neglect effect originated at the encoding stage: negative social feedback elicited smaller LPP amplitudes than positive feedback, which is in line with previous literature on the processing of social emotional materials (Bublatzky et al., 2014; Funkhouser et al., 2020; Gu et al., 2020) and the insufficient integration theory proposed by Pinter et al. (2011).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous previous studies using nonsocial materials (e.g., emotional words or pictures) have found comparable or even larger LPP amplitudes in negative, compared to positive, conditions (e.g., Schupp et al., 2000; for a review, see Hajcak et al., 2010). However, recent studies have demonstrated that the LPP amplitudes seem to show a different pattern when emotions are examined in social contexts, that is, larger LPP amplitudes were found following positive than negative social information (Bublatzky et al., 2014; Funkhouser et al., 2020; Gu et al., 2020). For instance, Funkhouser et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous studies (Funkhouser et al, 2019;Weinberg and Shankman, 2017), ERPs to feedback in the Doors Task differed as a function of condition, F(2, 114)=44.94, p<.001, R 2 =.12, such that mean amplitudes were significantly greater following monetary gain relative to both loss, t(114)=4.18, p<.001, semi-partial R 2 =.03, and neutral feedback, t(114)=9.46, p<.001, semi-partial R 2 =.12. Amplitudes were more positive following monetary loss than neutral feedback, t(114) = 5.28, p < .001, semi-partial R 2 =.04.…”
Section: Preliminary Analysessupporting
confidence: 92%
“…These residualized scores then control for activation that is common to processing both acceptance and rejection feedback, but may not represent a change from a neutral baseline. Future studies should consider the incorporation of non‐feedback trials or neutral feedback conditions; however, this too is challenging in social interaction paradigms, as there are individual differences in the interpretation of neutral interpersonal feedback (Meyer et al., 2004; Yoon & Zinbarg, 2008), as well as emerging evidence from the IG task that participants' neural responses to ambiguous feedback resemble their responses to rejection (Funkhouser et al, 2019). Moreover, prior research suggests that the RewP presents as a relative positivity to monetary reward, or the best possible local outcome in a task, and is less sensitive to differences between neutral and loss feedback (e.g., Kujawa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%